MHC Class I Cross-Presentation: Stage Lights on Sec22b. Issue 9 (September 2017) - Montealegre, Sebastian; van Endert, Peter
Abstract : Efficient (cross-)presentation of antigens internalized by dendritic cells (DCs) requires vesicular communication between the early secretory and the endocytic/phagocytic pathways, in which the Sec22b protein has been suggested to have a key role. Here, we undertake a critical assessment of two new studies that evaluate the role of Sec22b using gene-targeted mice and come to contradictory conclusions.